EFEITO DA VAPORIZAÇÃO EM MADEIRA DE Eucalyptus dunnii SOBRE ALGUMAS PROPRIEDADES MECÂNICAS - Severo, Elias Taylor Durgante [UNESP]; Tomaselli, Ivan (Universidade Federal de Santa Maria, 2000)
The aim of this study was to evaluate the vaporization effects on the crushing strength at limit of proportionality on perpendicular compression, crushing strength and modulus of elasticity in parallel compression to the fiber and shear strength (radial and tangential direction) on logs and sawn wood of two sources of Eucalyptus dunnii. The mechanical attempts were performed under the Copant standards in the climatized conditions (12%). To do so, about two thirds of the logs, with a diameter between 20-30 cm, were vaporized at 100o C and 100% of relative humidity for 20 hours, while the remaining logs were kept as control. From each log, a central plank radially directed with eight centimeter of thickness was taken, from which small beams of 8 cm x 8 cm were taken. Half of the small beams from the vaporized logs were once again submitted to vaporization under the same previously described conditions for a period of 3 hours, thus obtaining three different levels of comparison (control, vaporized on logs and presteaming wood). The results showed a remarkable reduction on the crushing strength in parallel compression to the fiber and shear strength (radial and tangential direction) with the vaporization on the two conditions and sources of Eucalyptus dunnii used. On the other hand, the crushing strength at limit of proportionality on perpendicular compression and modulus of elasticity in parallel compression did not show any change with the vaporization.

Este estudo teve como objetivo avaliar o efeito da vaporização em toras e madeira serrada de Eucalyptus dunnii sobre as propriedades de compressão paralela e perpendicular às fibras e cisalhamento no sentiod radial e tangencial aos anéis de crescimento. As razões do estudo deve-se à possibilidade de aliviar as tensões de crescimento existentes na espécie pelo emprego da vaporização. Os ensaios foram realizados na condição climatizada (12% de umidade). Para isso, dois terços das toras, com diâmetro entre 20 a 30 cm, proveniente de seis árvores por procedência dessa espécie foram vaporizadas a 100ºC e 100% de umidade relativa durante 20 horas, enquanto que as demais toras foram utizadas com controle. De cada tora foi retirada uma prancha central, orientada radialmente, de 8 cm de espessura, das quais se retirou vigotas de 8 cm x 8 cm. Metade das vigotas provenientes de toras vaporizadas foram novamente submetidas à vaporização, durante 3 horas, nas mesmas condições anteriormente descritas, obtendo-se, dessa forma, três níveis de comparação (controle, vaporizado em toras e madeira pré-vaporizada). Os resultados mostraram que o módulo de elasticidade em compressão paralela às fibras e o esforço no limite proporcional em compressão perpendicular as fibras não sofreram qualquer alteração com a vaporização. Entretanto a resistência máxima em compressão paralela as fibras e o cisalhamento (sentido radial e tangencial) mostraram reduzir significativamente com a vaporização.
WOOD VAPORIZATION EFFECT ON SOME MECHANICAL PROPERTIES OF Eucalyptus dunnii
Keywords: Eucalyptus dunnii; wood vaporization; perpendicular compression; parallel compression; Eucalyptus dunnii; vaporização da madeira; compressão paralela; compressão perpendicular